GREEN MARKETING: STRATEGIES FOR SUSTAINABLE BUSINESSES - Вишнівська, Богдана (SWorldJournal, 2024)
The topic of "Green Marketing: Strategies for Sustainable Businesses" explores the intersection of marketing practices and environmental sustainability. In this study, the main problems addressed include the environmental impact of traditional business mo